Ruthenium‐Catalyzed Hydroformylation of Alkenes by using Carbon Dioxide as the Carbon Monoxide Source in the Presence of Ionic Liquids. Issue 8 (7th July 2014) - Ali, Meher; Gual, Aitor; Ebeling, Günter; Dupont, Jairton
Abstract The reaction of [BMI⋅Cl] (BMI=1‐butyl‐3‐methylimidazolium) or [BMMI⋅Cl] (BMMI=3‐butyl‐1, 2‐dimethylimidazolium) with Ru3(CO)12 generates Ru–hydride–carbonyl–carbene species in situ that are efficient catalysts for a reverse water gas shift/hydroformylation/hydrogenation cascade reaction. The addition of H3PO4 increased the catalytic activity of the first step (i.e., the hydrogenation of CO2 to CO). Under the optimized reaction conditions [120 °C and 6.0 MPa CO2/H2 (1:1) for 17 h], cyclohexene and 2, 2‐disubstituted alkenes were easily functionalized to alcohols through sequential hydroformylation/carbonyl reduction.